Evaluación de riesgos ambientales producidos por el cambio climático de un bosque secundario en el centro de producción e investigación Pabloyacu - Panduro García, Viorica Isabel (2015)
In order to, find out basic answers. ls the world becoming a riskier place? Are the frequency and 1 or probability of threats and 1 or natural risks growing? Or is the nature and our forests are becoming more vulnerable to certain effects of climate change? And if is so, what are the effects that cause climate change impacts to this? This report identifies sorne risks that explain the problem or the effects of climate change. Geological and climatic characteristics make our region prone to natural hazards of extreme character. Furthermore, climate change is increasing the intensity and frequency of hydro-meteorological phenomena source, product of climatic variations occur - also increasingly convinced that the warming of the atmosphere there. On the other hand, a preliminary proposal for the practica! and adaptable development for the Evaluation of environmental risks caused by climate change in a secondary forest is proposed. lt should be noted that the identified risks such as forest tires, flooding, erosion and sliding evaluated results given as to future natural disasters, especially much of the green area for climate change in our region. Natural hazards identified should be directed to both prevention and mitigation, as a way to reduce vulnerability and impacts to future events. lt should be noted that this is a descriptive document according to the criteria of the thesis student. From the assessments made have analyzed the effect and 1 or environmental impact of climate change risk, using for this concepts and estimation procedures.